2007
DOI: 10.1038/sj.jid.5700624
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Epidermal Keratinocyte Differentiation by the Vitamin D Receptor and its Coactivators DRIP205, SRC2, and SRC3

Abstract: It has long been known that the active metabolite of vitamin D, 1,25 dihydroxyvitamin D(3), stimulates differentiation and inhibits proliferation in epidermal keratinocytes through interaction with the vitamin D receptor (VDR). VDR functions through the coordinate binding of vitamin D response elements in the DNA and specific coactivator proteins which help to initiate transcription. It was recently observed that VDR binds to two major coactivator complexes, DRIP (VDR-interacting protein) and SRC (steroid rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 14 publications
1
61
0
Order By: Relevance
“…Apart from exerting its classical functions, vitamin D receptor has been shown to exert antiproliferative actions in several different cancer cell lines (24,25). Recently, VDR has been implicated to play a broader role in the differentiation of epithelial keratinocytes and immunomodulatory activities (26,27). Although extensive work has been performed on the biological function of vitamin D and its analogs, little is known about the transcriptional regulation of VDR.…”
mentioning
confidence: 99%
“…Apart from exerting its classical functions, vitamin D receptor has been shown to exert antiproliferative actions in several different cancer cell lines (24,25). Recently, VDR has been implicated to play a broader role in the differentiation of epithelial keratinocytes and immunomodulatory activities (26,27). Although extensive work has been performed on the biological function of vitamin D and its analogs, little is known about the transcriptional regulation of VDR.…”
mentioning
confidence: 99%
“…The phosphatidylinositol 3-kinase (PI3-K)/Akt signaling has been implicated in 1,25(OH) 2 D 3 -induced differentiation of THP-1 human leukemia cells [62,89], HL60 cells [70,89e92] and keratinocytes, in which the membrane receptor for 1,25(OH) 2 D 3 is reported to be annexin II [67]. While in several studies [70,92] 1,25(OH) 2 D 3 was found to [412,413] Loricrin Late differentiation marker [409,410] Filaggrin Late differentiation marker [409,410] Cornified envelope formation [407,414] MUSCLE CELLS (C2C12) [93]. Likewise, vitamin D analogs downregulated Akt in SCC cells [94] and ErbB2 overexpressing mammary tumors [95], which was associated, respectively, with the anti-proliferative effect and inhibition of tumor growth.…”
Section: Phosphatidylinositol 3-kinase/akt Pathwaymentioning
confidence: 98%
“…1,25(OH) 2 D 3 is involved in all steps of this process in that it limits proliferation in the basal layer while inducing in a sequential pattern the expression of genes whose products ultimately produce the permeability barrier. The ability of 1,25(OH) 2 D to act sequentially on gene expression as the differentiation process unfolds is due to the differential distribution of coactivators (DRIP205 and SRC3) within the epidermis as a function of differentiation [87] and the differential utilization of these coactivators by genes involved in the early and late stages of differentiation [88]. CYP27b1 like VDR is found throughout the epidermis, although expression appears to be higher in the basal layer of the epidermis [19,28,29].…”
Section: Function Of Extra Renal Cyp27b1mentioning
confidence: 99%